If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5 = 7x + 3 Reorder the terms: -5 + 6x = 7x + 3 Reorder the terms: -5 + 6x = 3 + 7x Solving -5 + 6x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -5 + 6x + -7x = 3 + 7x + -7x Combine like terms: 6x + -7x = -1x -5 + -1x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -5 + -1x = 3 + 0 -5 + -1x = 3 Add '5' to each side of the equation. -5 + 5 + -1x = 3 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 3 + 5 -1x = 3 + 5 Combine like terms: 3 + 5 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| 119=7x-4(-4x+22) | | 2(v+2)-6v=24 | | 18x-7x-10x=2 | | 44(3+c)+c=c+4 | | p-p+p-p+4p=12 | | -30=4(u-8)-2u | | 5n+1p=1.06 | | sin^2x+2cosx=1 | | -3(u+5)=4u+48 | | x-0.13x=3500 | | -8u^2+28=0 | | 40x=61x | | 2x+3y+6z=360 | | 2/3(n−5/6)=21/2 | | 16x^5-44x^4+30x^3= | | 2x+63+7x+18=90 | | 3/4x=9/10 | | 5u+14=3(u+2) | | 6+9x= | | 20-14=g | | 640=5(2)*x | | .75x=1.25x | | 0=-8p-p^2-15 | | X^3-19x-20=0 | | 7(y-4)=9y-40 | | x/5x-40*x*x-8x/7= | | 3(4x+1)=9(2x-1) | | -6n(1+10n)= | | 0=11x-3x^2-10 | | -43=6b+8 | | 125m-100m+38800=40200-175m | | -6(x+3)-12=17+7 |